Supernumerary Teeth: Current Concepts and Clinical Implications (Academia Journal of Medicine, 2026)
Supernumerary teeth are developmental anomalies characterized by the presence of teeth  in excess of the normal dentition, occurring in both primary and permanent dentitions.  They are most commonly observed in the maxillary anterior region as mesiodens and  may lead to various complications such as delayed eruption, crowding, midline diastema,  and impaction of adjacent teeth. The etiology is considered multifactorial, with the  dental lamina hyperactivity theory being the most widely accepted, along with genetic  and syndromic associations. Advances in diagnostic techniques, particularly cone-beam  computed tomography, have significantly improved the localization and assessment of these  teeth, facilitating precise treatment planning. Management strategies range from periodic  observation to surgical removal, often followed by orthodontic intervention, with the  timing of extraction remaining a subject of ongoing debate. This review aims to provide  a comprehensive and updated overview of the etiology, classification, clinical features,  diagnosis, and management of supernumerary teeth, with emphasis on recent advances and  their clinical implications
Keywords: Supernumerary teeth; Dental anomalies; Management